INTEGRATED ANTI-RISK MANAGEMENT OF CONFLICTS OF A SCIENTIFIC PROJECT IN A BEHAVIORAL ECONOMICS - Bedrii, D. (Scientific Journal of Astana IT University, 2020)
The object of the research is the processes of managing uncertainties such as risks, conflicts, and factors of behavioral economics which may have negative consequences for a scientific project. The study has revealed that the success of any project depends on the ability of the project manager to effectively manage his team to meet the values of each stakeholder and the goals of the project itself. To solve this goal it is necessary to complete the following tasks: • analysis of methods of integration of risk management, conflicts and factors of behavioral economics; • justification of the necessity to build integrated anti-risk management of conflicts in behavioral economics; • to carry out conceptual modeling of integrated anti-risk conflict management in behavioral economics. A conceptual model of integrated anti-risk management of conflicts of a scientific project in the context of behavioral economics is proposed, built based on the “Change Management Iceberg” model. The management of scientific projects has been further developed through the integration of methodologies: project management, the theory of stakeholders, risk management, HR management, conflict management, and behavioral economics. A conceptual scheme of integrated anti-risk management of conflicts of a scientific project in behavioral economics has been developed which allows a project manager to manage uncertainties (risks, conflicts, factors of behavioral economics). Research refers to the project management methodology and improves it by integrating the processes of risk, conflict, and behavioral economics management into one process. The main goal of the study is to reduce and eliminate all negative consequences in a scientific project, to complete it within the approved budget, terms and a certain quality.